2016
DOI: 10.3389/fmicb.2016.00743
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Combination Screen Identifies Drugs Active against Amoxicillin-Induced Round Bodies of In Vitro Borrelia burgdorferi Persisters from an FDA Drug Library

Abstract: Although currently recommended antibiotics for Lyme disease such as doxycycline or amoxicillin cure the majority of the patients, about 10–20% of patients treated for Lyme disease may experience lingering symptoms including fatigue, pain, or joint and muscle aches. Under experimental stress conditions such as starvation or antibiotic exposure, Borrelia burgdorferi can develop round body forms, which are a type of persister bacteria that appear resistant in vitro to customary first-line antibiotics for Lyme dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 35 publications
8
85
0
2
Order By: Relevance
“…As the round of pulse dosing treatment with ceftriaxone increased, the number of spirochetal forms and round body forms decreased in the log phase culture ( Figures 1A–D ). We noted after the first round of ceftriaxone treatment the number of planktonic spirochetes decreased dramatically while the number of round body forms increased slightly presumably due to conversion of spirochetal form to round body forms (Feng et al, 2016a) in both the 5 day old late log phase and the 10 day old stationary phase cultures. Two and three rounds of treatment could kill both spirochetal form and round body forms, and the fourth round of treatment eliminated nearly all planktonic B. burgdorferi cells but still could not eliminate the aggregated microcolony form in the 10 day stationary phase culture ( Figure 1H ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…As the round of pulse dosing treatment with ceftriaxone increased, the number of spirochetal forms and round body forms decreased in the log phase culture ( Figures 1A–D ). We noted after the first round of ceftriaxone treatment the number of planktonic spirochetes decreased dramatically while the number of round body forms increased slightly presumably due to conversion of spirochetal form to round body forms (Feng et al, 2016a) in both the 5 day old late log phase and the 10 day old stationary phase cultures. Two and three rounds of treatment could kill both spirochetal form and round body forms, and the fourth round of treatment eliminated nearly all planktonic B. burgdorferi cells but still could not eliminate the aggregated microcolony form in the 10 day stationary phase culture ( Figure 1H ).…”
Section: Resultsmentioning
confidence: 87%
“…Our previous studies suggest that drug combination treatment is more effective than single drug treatment and could eradicate the B. burgdorferi microcolony forms in vitro (Feng et al, 2015a, 2016a,b) and that daptomycin showed best activity against stationary phase and round body form of B. burgdorferi (Feng et al, 2014a, 2016a). The daptomycin/doxycycline combined with cefoperazone or cefuroxime is the most effective drug combination which could eradicate even the most resistant aggregated microcolony form of B. burgdorferi enriched in stationary phase cultures (Feng et al, 2015a, 2016b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These atypical forms have been shown to have increased tolerance to doxycycline and amoxicillin when compared to the growing spirochetal forms [13,14,15,16]. In addition, that the active hits from the round body persister screens [18] overlap with those from the screens on stationary phase cells [13] indicates the stationary phase culture or cells can be used as a relevant persister model. Therefore, stationary phase cultures (seven to 15 days old) enriched in persisters have been used as a model for high-throughput drug screens against persisters [13,14,19].…”
Section: Introductionmentioning
confidence: 99%